2007
DOI: 10.3201/eid1312.070977
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiologic Characterization of WU Polyomavirus Infection, St. Louis, Missouri

Abstract: WU polyomavirus is a recently described polyomavirus found in patients with respiratory infections. Of 2,637 respiratory samples tested in St. Louis, Missouri, 2.7% were positive for WU polyomavirus by PCR, and 71% were coinfected with other respiratory viruses. Persistent human infection with WU polyomavirus is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 2 publications
11
49
3
Order By: Relevance
“…The rates of detection for the symptomatic children in our study are similar to those observed in prior studies (1,3,4). As in studies by others, we detected WUV in asymptomatic and symptomatic children (3)(4)(5)13). This fi nding provides further evidence that asymptomatic infection of WUV may occur.…”
Section: Discussionsupporting
confidence: 80%
“…The rates of detection for the symptomatic children in our study are similar to those observed in prior studies (1,3,4). As in studies by others, we detected WUV in asymptomatic and symptomatic children (3)(4)(5)13). This fi nding provides further evidence that asymptomatic infection of WUV may occur.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, in a large study carried out on 2,637 nasopharyngeal swabs or nasal washes, WUPyV was mainly detected in immunocompromised children. In some cases, WUPyV was the sole virus detected which suggests that the virus may be a respiratory pathogen (44). Murez et al (23), detected KIPyV and WUPyV in respiratory tract samples of severely immunocompromised patients.…”
Section: Kipyv and Wupyv Infection And Immunocompromised Patientsmentioning
confidence: 99%
“…As a result, a new polyomavirus was identified and subsequently recovered from symptomatic children in Australia and the United States. 96 Similarly, Palacios et al 97 used unbiased high-throughput sequencing to identify a previously unknown Old World arenavirus in specimens collected from 3 recipients of visceral organ transplants from a single donor, who each died of a febrile illness. These genome-based techniques should now be applied to highly important clinical scenarios, such as culture-negative sepsis or pneumonia, in which a bacterial infection is strongly suspected, but no known pathogens are recovered.…”
Section: Molecular Diagnostic Tests Are Developedmentioning
confidence: 99%